Sistem Informasi Event Budaya Solo Berbasis Android - Prayoga Umbulsari; Hartati Dyah W. (Go Infotech: Jurnal Ilmiah STMIK AUB, 2017)
Smartphone is chosen as a tool to implement information system of solo culture event due to observation in Solo city that shows that smartphone is owned by all people good from among children up to parents. Information Systems Solo Based Android Culture Event to provide information about events or events for the people of Solo city and tourists outside the city of Solo and as a medium of cultural promotion both national and international scale.Information Systems Solo Based Android Culture Event, built using descriptive method with the type of case study research in the city of Surakarta. Techniques of system weakness analysis using PIECES analysis (Perfomance, Information, Economy, Cotrol, Efficiency, and Service). For system development techniques using waterfall method, while to describe the data flow using Data Flow Diagram consisting of context diagram, Data Flow Diagram level 0 and Data Flow Diagram Level 1. Software used to build this system is Android Studiodan XAMPP as MySQL database connection . Based on testing that has been done using blackbox testing, the built system can help the problems faced Solo tourism office and Solo city tourists.Keywords: Cultural Event, Event Information System Android Based Culture, Android Studio, XAMPP